2015
DOI: 10.5774/44-0-172
|View full text |Cite
|
Sign up to set email alerts
|

“They Do Not Know Much, but Then, You Have to Cover the Syllabus”: The Quality Imperative – A Dilemma for Teachers’ in Early Grade Multilingual Classrooms in Kenyan Primary Schools

Abstract: The centrality of language in any education system cannot be overemphasised. Wolff (2006: 50) sums this up by stating that "language is not everything in education, but without language everything is nothing in education". As such, language mediates knowledge acquisition even when the content of education is not language. The question then arises as to which language is best to use in education. There are no straight answers to this, as education in most countries of the world takes place in multilingual con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In contrast, the second argument advocates for the further spread of English, as a globalised, powerful and prestigious language, which serves as an international tool that can lead to economic and professional success (Chetty & Mwepu, 2008;Guilherme, 2007;Potgieter & Anthonissen, 2017). Arguments about English being an international tool are among the main reasons why many parents prefer English as the MoI instead of their mother-tongues (D'Oliveira, 2013;Hornberger, 2002;Nyaga, 2013;Plüddemann, 2015;Setati, Adler, Reed & Bapoo, 2002). Various other reasons have been reported for English as a preference, such as a "deep suspicion" about mother-tongue education left by the Bantu Education Act during apartheid (Hornberger, 2002).…”
Section: Attitudes Toward Language-in-education Issues In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the second argument advocates for the further spread of English, as a globalised, powerful and prestigious language, which serves as an international tool that can lead to economic and professional success (Chetty & Mwepu, 2008;Guilherme, 2007;Potgieter & Anthonissen, 2017). Arguments about English being an international tool are among the main reasons why many parents prefer English as the MoI instead of their mother-tongues (D'Oliveira, 2013;Hornberger, 2002;Nyaga, 2013;Plüddemann, 2015;Setati, Adler, Reed & Bapoo, 2002). Various other reasons have been reported for English as a preference, such as a "deep suspicion" about mother-tongue education left by the Bantu Education Act during apartheid (Hornberger, 2002).…”
Section: Attitudes Toward Language-in-education Issues In South Africamentioning
confidence: 99%
“…A lack of teaching and learning material for the different languages Baker (2011);Bamgbose (1991in Nyaga, 2013; Kamwendo (2000); Stroud (2001) Teachers are not trained or proficient in teaching in the mother tongue of the learner Graham (2010) A lack of choice with regard to the MoI presented in schools due to a "take-itor-leave-it" attitude adopted by school governing bodies Boulleys (2014, p. 191) Fear of "separate language" development that could risk "social cohesion" Webb (2013, p. 180) Globalisation has increased the desire for English as the MoI instead of mother-tongue languages Webb (2013) The above discussion deals with two different views on the matter of the MoI at South Africa schools. However, using a MoI such as English that teachers are not proficient in or that the learners do not understand can significantly obstruct learning.…”
Section: Reasons For Implementation Challengesmentioning
confidence: 99%
“…Despite the misapprehension surrounding MT in African communities, a rich body of research on MTs has undoubtedly proved that, when children first achieve proficiency in their MT, they can learn the second language easier and faster (UNESCO 1953;Cummins 2001;Romaine 2013). The teaching and learning of MTs in Africa at large has, however, been challenged by both material and human resource issues (Bamgbose 1991(Bamgbose , 2004Woldemariam 2007;Chimbutane 2011;Nyaga 2013). Research on the teaching of MTs in various African countries has demonstrated that pupils/learners are very lively and are participative when they are taught in their MTs as opposed to second language(s) (Chimbutane 2011;Ssentanda 2014c).…”
Section: Introductionmentioning
confidence: 99%